Evaluation of water and sucrose diffusion coefficients in potato tissue during osmotic concentration - Mauro, M. A.; Menegalli, F. C. (Elsevier B.V., 2003)
The water and sucrose effective diffusion coefficients behavior were studied in potato tubers immersed in aqueous sucrose solution, 50% (w/,A), at 27 degreesC. Water and sucrose concentration profiles were measured as function of the position for 3, 6 and 12 h of immersion. These were adjusted to a mathematical model for three components that take into account the bulk flow in a shrinking tissue and the concentration dependence of the diffusion coefficients.The binary effective coefficients were an order of magnitude lower than those for pure solutions of sucrose. These coefficients show an unusual concentration dependence. Analysis of these coefficients as functions of the concentration and position demonstrates that, cellular tissue promotes high resistance to diffusion in the tuber and also the elastic contraction of material influences the species diffusion. (C) 2003 Elsevier B.V. Ltd. All rights reserved.
Keywords: mathematical model; concentration profiles; osmotic dehydration; shrinkage